Challenges by developer in lump sum procurement system - 275529 Tan, Patrick Paik Kuan (Skudai ; Universiti Teknologi Malaysia, 2003)
Thesis (Master of Science (Construction Management)) - Universiti Teknologi Malaysia, 2003